Integrally-skinned asymmetric membrane fabricated by blended polyimide/phthalonitrile-resin via nonsolvent induced phase separation - Tan, Jia Hui (Nanyang Technological University, 2022)
Polyimide is commonly used to fabricate dense membranes or porous substrates owing to its high mechanical strength, chemical resistance and easy structurability. However, fabrication of polyimides is difficult. Commercially available high performance polyimide, Matrimid 5218, has the advantage that it can dissolve in polar solvent in NMP in various concentration, making it a good candidate for membrane fabrication via Nonsolvent induced Phase Separation (NIPS) method. Phthalonitrile resins is also well known due to its excellent thermal and thermo-oxidative stability, and are used in composites, coatings, and adhesives. Although PN possess excellent high-temperature properties, the relative inflexibility of the resin system renders them unsuitable for many critical applications. To overcome the problems of these polymer, polymer blending is an approach to blend these polymers and fabricate an asymmetric membrane to obtain useful combination of properties derived from each component. The desired PNPI ISA membrane properties include defect free top layer, porous bottom layer, nonporous skin layer, low tortuosity pore structure (finger-like), and robust mechanical properties. However, research on blends of polyimide and phthalonitrile is rare as they are difficult to process. This study investigates not only PNPI blending behaviour, also their curing behaviour, morphology, miscibility, mechanical properties, and thermal properties by using FTIR, DSC, TGA, PLM, DMA and SEM. Based on the experiment results of the PNPI membranes fabricated via NIPS, defects were observed on the top layer and the bottom layer was not porous enough. Hence, by controlling the polymer to solvent ratio, PN concentration, as well as heat treatment temperature, membrane properties such as thermal stability and mechanical properties were improved. Morphology changes such as pore shrinkage were also observed on the SEM results. Improvements of thermal and mechanical properties were observed in the SEM, TGA, and DMA results respectively. The increase in strength, thermal stability and morphology was due to the crosslink effect of PN, which can be observed in the TGA, BET, and FTIR results. Additionally, the usage of PLM also showed that PN and PI are partially miscible yet able to attain uniform distribution. In the future, this study can be further improved to fabricate a PNPI membrane with high solvent resistance, selectivity, and permeability. The fabricated PNPI membranes may also be further improved to be used in nanofiltration and ultrafiltration.